Factors Affecting the Effectiveness of Literary Text Perception - Vashchenko, Iryna; Lytvynenko, Olena (East European Journal of Psycholinguistics, 2014)
The issues related to perception and understanding of different texts, especially literary ones are of interest for the researchers, who represent various scientific approaches and theories. Peculiarities of the reader’s work with the text, the author’s role in this process, mechanisms and components of perception and understanding of textual information were explored by experts from various fields of science, such as: psychology, linguistics, philosophy, sociology etc. The problem of text perception is connected with the issues of personal psychology, psychology of thinking, language and speech. Perception is a creative act of reflection the text image in the reader ’s mind. Furthermore, it is the subjectivization of the text content. Thus, the text is endowed with communicative, cognitive, informative, psychological and social characteristics which the reader has to realize. The peculiarity of such realization of textual information is determined not only by the content of the text, but also by the individual psychological characteristics of a person who perceives the information. Study of properties and manifestations, which can influence the process of literary text perception, opens up broad prospects not only to psychology, but also to a range of other scientific fields and spheres of practical activity. The article may be of interest to psychologists, literary critics, educators, PR and marketing specialists, and other professionals interested in the problems of human interaction with the text. References Granik, G. (1979). Psichologicheskaja Model Processa Formirovanija Umennii [Psychological Model of the Formation of Skills]. Voprosy Psychologii, 18, 64–69. Kamenskaya, O. (1990). Text i Kommunikatsija [Text and Communication]. Moscow: Vysshaya Shkola. Leontyev, A. (2003). Osnovy Psiholingvistiki [Fundamentals of Psycholinguistics]. Moscow: Smysl. Pashkovsky, V., Piotrovskaya, V., Piotrovsky, R. (2009). Psichiatrichescaja Lingvistica [The Psychiatric Linguistics]. Moscow: Librocom. Rubo, I. (1998). Psichologicheskiy Analiz Strategii Chteniya Nauchnogo Texta [Psychological Analyses of the Strategies of Scientific Text Reading]. Moscow.